THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING FOOD SAFETY AND QUALITY CONTROL - Rakhmonov Erkinjon; Kabilov Feruz (Western European Studies, 2024)
Artificial intelligence (AI) is revolutionizing the food industry by providing innovative solutions for enhancing food safety and quality control. This article explores the various applications of AI in improving food safety standards, detecting contaminants, predicting shelf life, and optimizing production processes. By harnessing the power of AI technologies such as machine learning, computer vision, and natural language processing, food manufacturers can ensure that their products meet regulatory requirements and consumer expectations. Furthermore, the integration of AI in quality control procedures is enabling realtime monitoring and rapid response to potential issues, ultimately leading to a more efficient and reliable food supply chain
Keywords: Artificial intelligence; Food safety; Quality control